Avaliação da publicidade de medicamentos veiculada nas principais emissoras de rádio de Natal-RN - Batista, Almária Mariz (2009)
Drugs advertising is one of the most important marketing resources used by the pharmaceutical industry to induce people to buy these products although they do not have the real necessity to use them. The purpose of this article is to evaluate drugs advertisings transmitted on radio stations in Natal/RN, from October 2007 to September 2008. Were collected 228 advertising pieces, where, 21 were different among themselves and corresponded to 15 drugs. The results showed that 73,3% of the drugs ads were announced on AM station and 26,7% on FM station. The majority of the drugs were constituted of analgesics (26%), following by antiacids, vitamins, phitotherapics (13% each). The legal analysis showed that each advertising had some kind of infraction. The omission of the registration number happened in each advertising, following by the totally lack of contraindications (95,2%) and contraindications DCB/DCI (76,2%). In 42,9% advertisements were observed the relation between drugs use and physique/intellectual/emotional/sexual performance and/or beauty and 33% of them had abusive exploration of illnesses. The obligatory warning was omitted in 28,6% and the offer of financial bonus happened in 9,5% cases. The content analysis demonstrated that the most persuasion and convincing elements observed were indicatives of consumption appeal (34,2%). The study indicates the necessity of the topic drugs advertisements to be treated in a wide context, that is, to be discussed as a public health concern. Although the advertising regulation and inspection is the State responsibility , this should be shared with the advertising agency, pharmaceutical industry and media. Furthermore, it is indispensable to inform and to conscience the population of their rights in such mistaken situation